PATHOLOGY OF RESPIRATORY TRACT DISEASES IN NEWBORN BABIES - Nuritdinova Gavkhar Toipovna (Scholar Express Journals, 2024)
Bronchial asthma (BA) is a systemic allergic disease and is associated with pathology of the upper respiratory tract (URT). In recent years, attention has been focused on the multimorbidity of allergic diseases, while the spectrum of URT pathology in children with asthma has not been sufficiently characterized. The purpose of the study was to study the structure of the pathology of the upper respiratory tract in children with atopic asthma. Materials and methods of research: 358 children with atopic asthma were examined, the average age of the children was 9.91 (9.47; 10.35) years, of which 67.9% (192/358) were boys, as well as 108 children with complaints of nasal breathing disorders, comparable by age and gender, but without asthma
Keywords: bronchial asthma; upper respiratory tract; hypertrophy of the pharyngeal tonsil